Speculation and the Bond Market: An Empirical No-Arbitrage Framework - Barillas, Francisco; Nimark, Kristoffer (Management Science, 2019)
An affine no-arbitrage asset pricing framework is developed that allows for agents to have rational but heterogeneous expectations. The framework can match both bond yields and the observed dispersion of yield expectations in survey data. Heterogeneous information introduces a speculative component in bond prices that is (i) statistically distinct from classical components such as risk premia and expectations about future short rates and (ii) quantitatively important, at times accounting for up to 125 basis points of U.S. yields. Allowing for heterogeneous expectations also changes the estimated relative importance of risk premia and expectations about future short rates in historical bond yields compared to a standard affine model. The framework imposes weaker restrictions than existing heterogeneous information asset pricing models and is thus well suited to empirically quantify the importance of relaxing the common information assumption. This paper was accepted by Tomasz Piskorski, finance.